A Hydrogen‐Bonded Cyanide‐Bridged [Co2Fe2] Square Complex Exhibiting a Three‐Step Spin Transition. (7th December 2016) - Nihei, Masayuki; Yanai, Yuta; Hsu, I.‐Jui; Sekine, Yoshihiro; Oshio, Hiroki
Abstract: Co‐crystallization of a cyanide‐bridged tetranuclear complex [Co2 Fe2 ] with 4‐cyanophenol (CP) gave a hydrogen bonding donor–acceptor system, [Co2 Fe2 (bpy*)4 (CN)6 (tp*)2 ](PF6 )2 ⋅2 CP⋅8 BN (1 ).1 exhibited a three‐step phase transition between HT, IM1, IM2, and LT phases upon temperature variation. Variable temperature magnetic measurements and structural analyses revealed that the three‐step spin transition is caused by electron‐transfer‐coupled spin transitions (ETCSTs) accompanied with alteration of the hydrogen bonding interactions.